Evaluation of the European strategy on safety and health at work 2007-2012. Final report (Brussels, 2013)
"The Evaluation of the European strategy on Safety and Health at Work 2007-2012 was commissioned by the European Commission's Directorate General for Employment, Social Affairs & Inclusion and carried out by COWI (from Denmark), Milieu (from Belgium) and the Institute of Occupational Medicine (IOM - from Great Britain). The overall objective of the evaluation was to provide a sound and evidence-based evaluation of the 2007-2012 EU strategy on safety and health at work and to provide reasoned recommendations for the development of future EU policy instruments in this area (e.g. a new post-2012 strategy). The main conclusion in respect to the relevance of the current strategy is that it has been relevant and its merits have especially been in providing a clear policy basis and framework for coordination, and a common sense of direction for many of the actors involved in the OSH policy area. The strategy served as an important policy signal and driver for national action on OSH and also facilitated useful coordination in respect to public health initiatives. However, there remains room for improvement in the integration and coordination between OSH and other policy areas and between the various actors involved at the EU level. In particular, coordination with environmental policy and the important area of the REACH regulation on chemicals and their safe use has been inadequate. Also, the articulation between the strategy implementation and the European social dialogue has been limited and European social partners have felt a limited degree of ownership towards the strategy and have mainly implemented those parts of the strategy which they would have implemented in any case. The evaluation concluded that there is a need to continue to focus on the persisting issues related to occupational health and safety, which exist throughout the EU. This should be seen in conjunction with the EU strategies for economic growth, most notably the EU2020 agenda. There is also a need for a stronger integration of a new strategy with broader EU health and environmental strategies (in particular), through enhanced coordination with other DGs. The evaluation also recommended that a new strategy should focus clearly on musculoskeletal disorders, stress and occupational cancer deaths and should target in particular the challenges related to the implementation of the legal framework with an explicit focus on SMEs and micro-enterprises."